2018
DOI: 10.21873/cgp.20073
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Novel Prognostic and Possible Predictive Biomarkers of Lung Neuroendocrine Tumors

Abstract: The mammalian target of rapamycin (mTOR) pathway plays a key role in cellular processes by regulating protein synthesis, cell growth and metabolic systems. Deregulation 153

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Several molecular alterations in thoracic neuroendocrine tumors interfere with cell-cycle regulation, chromatin remodeling, apoptosis, intracellular cascades, and cell–cell interactions. However, molecular alterations in thoracic neuroendocrine tumors that might be considered as targets for treatment are very scarce, and treatment of pulmonary and thymic carcinoids on a personalized basis is still an unmet goal, despite a list of hypothetical biomarkers [ 101 ]. Among those, rovalpituzumab tesirine, which targets the inhibitory Notch ligand Delta-like protein 3 (DLL3), has been shown to be a promising therapeutic agent in pulmonary neuroendocrine carcinomas.…”
Section: Implications For Therapymentioning
confidence: 99%
“…Several molecular alterations in thoracic neuroendocrine tumors interfere with cell-cycle regulation, chromatin remodeling, apoptosis, intracellular cascades, and cell–cell interactions. However, molecular alterations in thoracic neuroendocrine tumors that might be considered as targets for treatment are very scarce, and treatment of pulmonary and thymic carcinoids on a personalized basis is still an unmet goal, despite a list of hypothetical biomarkers [ 101 ]. Among those, rovalpituzumab tesirine, which targets the inhibitory Notch ligand Delta-like protein 3 (DLL3), has been shown to be a promising therapeutic agent in pulmonary neuroendocrine carcinomas.…”
Section: Implications For Therapymentioning
confidence: 99%
“…One of the reasons for this is the low prevalence of this disease. MiRNA expression among patients with NEN of the pancreas, small intestine, stomach and lung cancer have been studied [7,16,18,21,22,24,25,28,35,36,40,46,[48][49][50].…”
Section: Localization Of Nen Increased Expression Decreased Expression Citationmentioning
confidence: 99%
“…Molecular markers based mainly on the functional characteristics of genes are widely studied, and the results are summarized, for example, in [7]. Much remains to be studied and analyzed regarding miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some studies have showed how the genetic alterations of TC differ from those of AC [ 13 , 14 ]. A study conducted with next generation sequencing (NGS) on 148 lung NENs, including 88 TC and AC, demonstrated that MEN1 alterations were almost exclusive to WD Lu-NETs, whereas alterations of TP53 and RB1 genes were significantly enriched in SCLC and LCNECs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%